2022
DOI: 10.3389/fpubh.2021.823739
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Body Mass Index and Dyslipidemia on the Relation of Uric Acid and Type 2 Diabetes: Results From China Health and Retirement Longitudinal Study

Abstract: ObjectiveThis study assessed temporal relationships of serum uric acid (SUA) with blood glucose and determine the mediating effects of body mass index (BMI) and dyslipidemia on the relation of SUA and risk of type 2 diabetes.MethodsParticipants aged ≥ 45 years were participated in 2011 and followed up until 2015. Cox proportional hazards regression with a robust variance estimator was performed to explore the association of SUA with the risk of diabetes, and crosslagged path analysis was introduced to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In contrast, among the Asian population, including the Chinese people, mixed results were revealed ( 8 11 ). Using the multinomial logistic regression model, we observed that hyperuricemia was an independent risk factor for prediabetes but not diabetes among adults (aged between 35 and 75 years).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In contrast, among the Asian population, including the Chinese people, mixed results were revealed ( 8 11 ). Using the multinomial logistic regression model, we observed that hyperuricemia was an independent risk factor for prediabetes but not diabetes among adults (aged between 35 and 75 years).…”
Section: Discussionmentioning
confidence: 93%
“…SUA is related to BMI and diabetes, and obesity is considered a mediator in the association between hyperuricemia and diabetes ( 16 ). A recent study showed that high BMI and dyslipidemia significantly mediated the association in women ( 11 ). Elevated SUA is significantly associated with hyperlipidemia ( 19 ) and a higher percentage of fat accumulation in the liver ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, compared with other chronic diseases, hypertension and dyslipidemia are more likely to lead to diabetes, and diabetes also likely leads to the occurrence of hypertension or dyslipidemia [ 51 , 52 , 53 ]. As the main component of metabolic syndrome, diabetes, hyperglycemia, and hyperlipidemia interconnect and influence each other, forming a complex framework of chronic diseases [ 54 ]. With the prolongation of the disease’s course, the patient’s body’s immune function becomes increasingly abnormal, the function of many systems is weakened, and multiple diseases are prone to occur.…”
Section: Discussionmentioning
confidence: 99%